Clinical results of anterior cruciate ligament reconstruction with bone-patellar tendon-bone autograft: A prospective study (Annals of Medical Research, 2021)
None
Keywords: Anterior Cruciate Ligament Rupture; Knee Arthroscopy; Sport Injury.